Establishment and application of a quadruple target real-time PCR assay for detecting Yersinia pestis - Wenfang Wang; Xiaoxue Zhang; Hui Yu; Zhanli Wang (PLoS ONE, 2026)
In order to establish an efficient method for high-throughput detection of Yersinia pestis (Y. pestis) , a quadruple target real-time polymerase chain reaction assay was developed based on the specific target genes of Y. pestis ( caf1 , pla , ymt , and ypo-1094 ). Its sensitivity, specificity, and repeatability were evaluated, and clinical serum samples were tested by the established method. The results showed that no cross-reactivity was observed with other bacterial nucleic acids. The optimal linear detection range for caf1 , pla , ymt , and ypo-1094 was 12.09 × 10 - ⁶-12.09 × 10 1 ng/μL, and the lower limit of detection was 12.09 × 10 −4 ng/μL. Four different DNA concentrations of caf1 , pla , ymt , and ypo-1094 (10 −4 , 10 −3 , 10 −2 , 10 −1 and 10 1 ng/μL) were tested five times, achieving good repeatability. In the clinical sample detection, all the Y. pestis – positive samples were identified. The established method has potential for clinical use for rapid detection of Y. pestis with high specificity and high sensitivity.